The Relationship Between Mothers' Participation Level in Integrated Health Posts (Posyandu) and the Nutritional Status of Toddlers - Rukmasari, Ema Arum; Maesaroh, Imas; Mamuroh, Lilis (GoAcademica Research & Publishing, 2024)
Mother's participation in posyandu is one of the efforts to monitor the nutritional status of children under five. However, there are still mothers who do not use health facilities for their toddlers. The purpose of this study was to determine the relationship between the level of participation of mothers in Posyandu and the nutritional status of children under five. The research method with retrospective cohort approach. The population in this study were 422 mothers with a study sample of 215 mothers. Random sampling technique. The Instrument of Nutritional Status of Children Based on Index was used in this study. Univariate and bivariate analysis of Kendall's tau_b is the analysis of the data used. The results of this study showed that the participation of active mothers to posyandu amounted to 172 people (80%) and inactive as many as 23 people (13%). The nutritional status of toddlers in Sindangkasih Village is mostly in the category of nutritional status at risk of nutrition of more than 129 toddlers (60%), good nutrition of 38 toddlers (17.7%), poor nutrition of 38 toddlers (17.7%), malnutrition of 7 toddlers (3%), nutrition of more than 2 toddlers (0.9%), and obesity of 1 toddler (0.5%). There was no relationship between maternal participation rates and the nutritional status of toddlers and gis. 0.310 > 0.05. The conclusion of the study was that there was no relationship between maternal participation and the nutritional status of toddlers with p = 0.310 > 0.05. This can be caused by a lack of knowledge and attitudes of mothers towards the nutritional status of toddlers. Community Health Centers can conduct outreach and counseling to cadres and mothers who use health services to detect nutritional problems, including malnutrition, as early as possible.